Theoretical analysis of breakdown probabilities and jitter in single-photon avalanche diodes - Tan, S. L.; Ong, D. S.; Yow, H. K. (AMER INST PHYSICS, 2007)
A simple random ionization path length model is used to investigate the breakdown probabilities and jitter in single photon avalanche diodes (SPADs) with submicron multiplication widths. The simulation results show that increasing the multiplication width may not necessarily increase the breakdown probability relative to the breakdown voltage, as the effect of dead space becomes more dominant in thinner multiplication regions at realistic ionization threshold energies for GaAs. On the other hand, reducing the multiplication width results in smaller breakdown time and jitter, despite the increased dead space. The effect of dead space in degrading breakdown time and jitter is relatively weak and further compensated by the stronger influence of large feedback ionization at high fields. Thus, SPAD designs that can minimize the dark count rate may potentially benefit from enhanced breakdown probability, breakdown time, and jitter by reducing the thickness of the multiplication region. (C) 2007 American Institute of Physics.